DRUG UTILIZATION PATTERN STUDY IN YOUNG ADULT PATIENTS OF CUTANEOUS ADVERSE DRUG REACTIONS - Nagaratnam, C.; Deepika, B.; Deepalatha, C. (International Journal of Current Pharmaceutical Research, 2018)
Objective: To evaluate prevalence of cutaneous adverse reactions in young adult age group using ADR notification form. To create awareness in hospitals and health sectors, to establish drug safety monitoring units for mother and child care. Methods: Individual case safety reports of 46 patients from various hospitals were analyzed using CDSCO forms. To tabulate data on drugs, doses, systems, ADRs and factors for causation of cutaneous ADRs. Results: Females are more prone compared to males due to pregnancy at young age with increased use of Iron combinations, antibiotics and antiepileptic's in young adult age groups (20-30yrs) among cutaneous ADRs. Conclusion: We conclude the need for establishment of drug safety units with generic units for maternity sections and use of drugs in pre and post natal period, as pregnancy and adult age are risk factors for cutaneous adverse drug reactions. Every hospital structure needs special caution on drug lots of iron preparations, antibiotics, analgesics, antiepileptic's to be used in Obstetrics and Gynecology departments.